Environmental health risks and impacts of PM2.5 exposure on human health in residential areas, Bantul, Yogyakarta, Indonesia - Azham Umar Abidin; Anisful Lailil Munawaroh; Aulia Rosinta; Arvi Tri Sulistiyani; Iwan Ardianta; Fajri Mulya Iresha (Toxicology Reports)
Air pollution, particularly PM2.5, significantly impacts public health in developing areas. This study evaluates PM2.5 exposure among residents and conducts a health risk assessment within the human community in Bantul Regency, Indonesia, utilizing a high-volume air sampler (HVAS) over 24 h in a residential area and interviewing 36 respondents. The findings of this study show that PM2.5 concentrations varied from 50.7 to 61.9 μg/m³, exceeding the national ambient air quality standards (NAAQS) of 35 μg/m³. The risk hazard quotient (RQ) values of PM2.5 were greater than 1, signifying considerable health risk. Epidemiological statistical analysis indicates a significant correlation (p-value < 0.05) between PM2.5 exposure, health complaints, and respondent characteristics. Residents report health issues including cough, headache, eye irritation, breathlessness, and wheezing. The findings emphasize the imperative for more rigorous air quality standards and regulations, enhanced public awareness and education regarding preventive practices, and urban planning development strategies incorporating green infrastructure. These measures are crucial for alleviating health hazards and enhancing air quality in impacted areas.